Dynamic analysis of a hydro-motor drive system using priority valve. (June 2019) - Kumar, Sujit; Dasgupta, K; Ghoshal, SK; Das, J
The priority valve is considered to be one of the critical parts of the hydraulic system used in mining equipment. This article analyzes the dynamic performance of a hydro-motor drive system using priority valve through system modeling and simulation. A typical hydraulic system of a mining equipment is considered for the analysis, where a stable source of flow is supplied to two hydro-motors through priority flow divider valve. Bondgraph simulation technique is used for the modeling of the complete system, which is validated experimentally. The influences of some key parameters on the transient response of the system have been studied through simulation. The work presented in this article forms the basis idea for the design and optimization of the priority flow control valve for a given application.